1974
DOI: 10.1104/pp.54.3.294
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Oat Leaves during Senescence

Abstract: When the detached first leaves of green or etiolated oat (Avena sativa cv. Victory) seedlings senesce in the dark, their oxygen consumption shows a large increase, beginning after 24 hours and reaching a peak of up to 2.5 times the initial rate by the 3rd day. This effect takes place while the chlorophyll of green leaves, or the carotenoid of etiolated leaves, is steadily decreasing. Kinetin, at a concentration which inhibits the decrease in pigment, completely prevents the respiratory rise; instead, the oxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
1

Year Published

1975
1975
1983
1983

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(61 citation statements)
references
References 24 publications
4
56
1
Order By: Relevance
“…3A). Starch does accumulate in primary leaves of barley (unpublished data) or oats (16). A basipetal translocation of amino acids, but not soluble sugars, occurs when oat leaves senesce (19).…”
Section: And Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). Starch does accumulate in primary leaves of barley (unpublished data) or oats (16). A basipetal translocation of amino acids, but not soluble sugars, occurs when oat leaves senesce (19).…”
Section: And Discussionmentioning
confidence: 99%
“…The rapidity of the stomatal response suggests that hormonal influences may be important here. Application of hormones to senescing leaves has a pronounced effect on stomatal resistance (17) and phenomena intimately associated with CO2 assimilation or evolution, such as RuBPCase (12,25), RuBPCase activity (12), and dark respiration (16,18 …”
Section: And Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…it is dependent on some synthetic processes, probably formation of enzymes, at the start. There is evidence that the increased respiration is due to an uncoupling phenomenon and that cytokinins act to maintain the tightness of the coupling (33). It has also been found that proteolysis precedes the beginning of loss of Chl by some 18 to 20 hr at 25 C, and that levels of two proteinases in these leaves increase during senescence, an increase which is prevented by cycloheximide (21).…”
mentioning
confidence: 97%
“…As will be shown, the antibiotics are not without an effect on senescence. Each of the 12 concave wells in a porcelain plate received one such 0.25-ml preparation; the plate rested on moist filter paper in a 14-cm Petri dish, and was either left in the growth chamber at 25 C in the dark or exposed to fluorescent white light of (21,33), and Michael (22) deduced that the protein-Chl ratio remained constant during leaf senescence. The probable explanation for the large difference here is that in the chloroplasts, but not in the leaf, the Chl is subjected to photooxidation, and this will be confirmed below.…”
mentioning
confidence: 99%